Preparation and characterization of copolyesters of poly(tetramethylene succinate) and poly(butylene terephthalate) - Pisula, W.; Pigłowski, J.; Kummerlöwe, C. (Polimery, 2022)
Polymer blends of poly(tetramethylene succinate) (PTMS), a biodegradable aliphatic polyester, and poly(butylene terephthalate) (PBT), a non-biodegradable polyester with aromatic elements, were prepared by melt mixing. Transesterification reactions between both polyesters were promoted by the addition of zinc acetate as a catalyst. The transesterification reaction was evaluated by FT-IR measurements combined with solubility tests and 1H NMR spectroscopy. The molecular structure of the copolyesters is influenced by the catalyst content and the initial blend composition. Thermal and mechanical properties and the morphology of the resulting material were characterized.